EVALUASI KEBIJAKAN SIMANTRI DI KECAMATAN KINTAMANI, BANGLI. (Kajian Komparasi: Simantri â€œ278â€ Desa Abuan dan Simantri â€œ113â€ Desa Mengani Tahun 2014) - Santikasari, Ni Putu Budi; Bandiyah, Bandiyah; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2016)
ABSTRACT The purpose of this research is to get the actual picture about Simantri's Program evaluation at Kintamani's district, Bangli The method of this research is qualitative comparability to understand how simantri have differences in results between Abuan and Mengani. To collect the data this research use interview, observation, and documents. The result founded in this research which is, performing failing Programs Simantri at Mengani village because of some factor which is, lack of farmer group participations, communication that insufficiently effective among associate and farmer's group member, so the knowledge, attitude, and farmer member action in activity performing programs still less according to working procedure which be applied. Keyword :Public policy, Evaluate Public policy, Simantri's program